Money Replenishment Data Collection System at ATM Machine Managed by PT. Advantage Supply Chain Management in Medan City - Fajar Chrisman Ziliwu; Sri Wahyuni; Akhyar Lubis (Sean Institute, 2022)
Replenishment of money at the ATM machine always happens every day. PT. Advantage SCM is a company assigned to top up money at ATM machines. Replenishment schedules are carried out every day for ATM machines that do not have a balance anymore. ATM filling needs to be recorded every time the machine is refilled. The author builds an information system to record the activities of charging money at the ATM machine to assist the relevant teams in improving team performance. Every day there are approximately 30 ATM machines that will be filled with money because they are empty. This activity must be recorded properly so that the daily report does not become a problem in the future.